Embodied emotions in ancient Neo-Assyrian texts revealed by bodily mapping of emotional semantics - Lahnakoski, Juha M.; Bennett, Ellie; Nummenmaa, Lauri; Steinert, Ulrike; Sams, Mikko; Svärd, Saana (Elsevier BV, 2025)
Emotions are associated with subjective emotion-specific bodily sensations. Here, we utilized this relationship and computational linguistic methods to map a representation of emotions in ancient texts. We analyzed Neo-Assyrian texts from 934–612 BCE to discern consistent relationships between linguistic expressions related to both emotions and bodily sensations. We then computed statistical regularities between emotion terms and words referring to body parts and back-projected the resulting emotion-body part relationships on a body template, yielding bodily sensation maps for the emotions. We found consistent embodied patterns for 18 distinct emotions. Hierarchical clustering revealed four main clusters of bodily emotion categories, two clusters of mainly positive emotions, one large cluster of mainly negative emotions, and one of empathy and schadenfreude. These results reveal the historical use of embodied language pertaining to human emotions. Our data-driven tool could enable future comparisons of textual embodiment patterns across different languages and cultures across time.